Line balancing of aircraft IDG part maintenance process line balance using line balancing and promodel - Nyimas Desy Rizkiyah; Rivandi Ainul Putra; Yusril Ihza Muhammad; Mega Purnamasari (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Aircraft have thousands of components that must be maintained to remain functional. Components on aircraft have a high enough price that maintenance is required. The power source on an airplane can be divided into 2 types, namely AC and DC. One source of AC electricity is the Integrated Drive Generator (IDG) which is one of the important components of an aircraft that functions as a generator of electricity. If IDG experiences a problem, it will disrupt aircraft operations. For this purpose, IDG must receive good care with effective services. The processing time for maintenance services takes 42.8 hours for one IDG part unit. This study aims to balance the trajectory. The IDG part maintenance process is carried out by Pro-model simulation. The results of the IDG maintenance simulation are the maintenance time in operation (Average time in Operation) which is 42.61 hours and the IDG parts handled are 11 IDG parts. The results of this simulation scenario can estimate the possible number of IDG parts that will occur annually and can estimate the total service capacity that handles the planned number of incoming entities. The best scenario results when the capacity of 1 service group per unit will result in the number of IDG maintenance services of 11 units per year, by increasing the service capacity to 2 service groups per unit will result in the number of IDG maintenance services of 23 units per year. And by increasing the service capacity to 4 service groups per unit, the number of maintenance services will be 46 units per year.